Stomata coordinate with plant hydraulics to regulate transpiration response to vapour pressure deficit in wheat - Ranawana, S.R.W.M.C.J.K.; Siddique, K.H.M.; Palta, J.A.; Stefanova, Katia; Bramley, H. (CSIRO, 2021)
Genotypic variation in transpiration (Tr) response to vapour pressure deficit (VPD) has been studied in many crop species. There is debate over whether shoots or roots drive these responses. We investigated how stomata coordinate with plant hydraulics to mediate Tr response to VPD and influence leaf water status in wheat (Triticum aestivum L.). We measured Tr and stomatal conductance (gs) responses to VPD in well-watered, water-stressed and de-rooted shoots of eight wheat genotypes. Tr response to VPD was related to stomatal sensitivity to VPD and proportional to gs at low VPD, except in the water-stressed treatment, which induced strong stomatal closure at all VPD levels. Moreover, gs response to VPD was driven by adaxial stomata. A simple linear Tr response to VPD was associated with unresponsive gs to VPD. In contrast, segmented linear Tr to VPD response was mostly a function of gs with the breakpoint depending on the capacity to meet transpirational demand and set by the shoots. However, the magnitude of Tr response to VPD was influenced by roots, soil water content and stomatal sensitivity to VPD. These findings, along with a theoretical model suggest that stomata coordinate with plant hydraulics to regulate Tr response to VPD in wheat.